Implementasi Cross Cultural Understanding Praha-Suchdol, Czech Republic dan Prodi Sastra Inggris dan Seni Musik Universitas HKBP Nommensen di Kota Medan - Pasaribu, Arsen Nahum; Jakub Širlo Jednostranná; Žaneta Kváčová Budovatelů; Martina Holcová Libeř, Libeň č.p; Jubilizer Sihite; Kartini Manalu; Donna Pasaribu; Ardiwan Halawa; Happy Waruwu; Eston Hernandes Panggabean (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
This Cross Cultural Understanding activity is part of a Community Service Program (Pengabdian kepada Masyarakat or PKM) aimed at introducing the local culture of Medan City to students and lecturers from Praha-Suchdol, Czech Republic, through collaboration with the English Literature and Music Arts Study Programs of Universitas HKBP Nommensen. This activity was designed as an effort to strengthen intercultural understanding, enhance appreciation of diversity, and foster academic and cultural relations between countries. The implementation method involved direct visits to two main cultural sites—Istana Maimun and Velangkanni Church—with local students actively serving as cultural guides. The results of the activity showed meaningful educational interactions, where international participants gained firsthand insights into Indonesian culture, while local students developed intercultural communication skills and a deeper sense of pride in their cultural identity. This program demonstrates that cultural introduction through direct experience can be an effective strategy for building tolerance and sustainable international collaboration.